Community of Women Enterpreneurs: The Role of Competitive Advantage in Improving Marketing Performance - Aprih Santoso; M. Rikza Chamami (Prosperity: Journal of Society and Empowerment, 2023)
The research aims to empirically analyze the influence of digital marketing on marketing performance with product competitive advantage as a mediating variable in the community of women creative industry entrepreneurs in Pedurungan District, Semarang City. The research sample used was 117 people obtained using the census method sampling technique. Data collection was carried out by survey using a questionnaire. The relationship model between variables will be analyzed using path analysis through the SPSS version 26 program. Based on the test results, the results show that digital marketing has a significant and positive effect on marketing performance and competitive advantage as a mediating variable capable of mediating the influence of digital marketing on marketing performance in the community of industrial women entrepreneurs. creative in Pedurungan District, Semarang City.